Diverging stories of son preference in South Asia: a comparison of India and Bangladesh - Huq, Lopita; Kabeer, Naila; Mahmud, Simeen (BRAC University, 2013)
In Bangladesh, overall sex ratio has declined from 109.6 (males/females) in the 1950s to 100.3 in 2011. Unlike countries with female deficits, the improvement in sex ratio has extended to the under‐5 age group. This has happened in a context where per‐capita income has grown modestly but poverty continues to be widespread. Thus the story of “missing women” is evolving differently in Bangladesh than from India where decline in overall sex ratios has been accompanied by worsening of child sex ratios. In this paper we explore the hypothesis that improvement in child sex ratios in Bangladesh is due to a shift in parental preferences about sex composition of families in a society undergoing rapid socio‐economic change. Using a combination of quantitative and qualitative data, we find that parents are less likely to discriminate between sons and daughters than in the past with respect to survival and investments in human capital. These changes indicate a weakening of patriarchal structures and cultural norms around fertility intentions and sex composition of families. In comparison to India, it is speculated that the diverging story of sex preference in Bangladesh could be related to the timing of introduction of sex selection technology and the role of the state and civil society in the two contexts.